The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/feart.2019.00085
|View full text |Cite
|
Sign up to set email alerts
|

Diazotrophy Drives Primary Production in the Organic-Rich Shales Deposited Under a Stratified Environment During the Messinian Salinity Crisis (Vena del Gesso, Italy)

Abstract: Density stratification between freshwater and brine is periodically formed during massive evaporation events, which often associates deposition of organic-rich sediments. Here, we investigated phototrophic communities and nitrogen cycle during the deposition of two organic-rich shale beds of gypsum-shale alternation, representing the initial stage of the Messinian salinity crisis (Vena del Gesso, Northern Apennines, Italy). The structural distributions and the carbon and nitrogen isotopic compositions of geopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 85 publications
(122 reference statements)
2
12
0
Order By: Relevance
“…These results agree with recent hydrological models (de Lange & Krijgsman, 2010;Simon & Meijer, 2017;García-Veigas et al 2018). In contrast, only a few geochemical data are available for the sediments deposited during the early stages of the MSC (Kenig et al 1995;Sinninghe Damsté et al 1995b;Isaji et al 2019a). These studies all describe organic-rich shales of the PLG unit, depicting a stratified basin that received freshwater from rivers (Natalicchio et al 2017(Natalicchio et al , 2019Sabino et al 2020) and/or low-salinity water from the Paratethys (Grothe et al 2020).…”
Section: Introductionsupporting
confidence: 86%
“…These results agree with recent hydrological models (de Lange & Krijgsman, 2010;Simon & Meijer, 2017;García-Veigas et al 2018). In contrast, only a few geochemical data are available for the sediments deposited during the early stages of the MSC (Kenig et al 1995;Sinninghe Damsté et al 1995b;Isaji et al 2019a). These studies all describe organic-rich shales of the PLG unit, depicting a stratified basin that received freshwater from rivers (Natalicchio et al 2017(Natalicchio et al , 2019Sabino et al 2020) and/or low-salinity water from the Paratethys (Grothe et al 2020).…”
Section: Introductionsupporting
confidence: 86%
“…Our method has the capacity to determine δ 13 C and δ 15 N values of both major and minor geoporphyrin types found in ancient sediments, especially for nitrogen, which only requires 0.15 μgN to achieve the analytical precision described earlier. The isotopic compositions of minor but more source-specific geoporphyrins, such as that derived exclusively from chlorophyll c or those derived from bacteriochlorophyll d or e homologues, , provide a much more detailed snapshot of the primary producers and the carbon and nitrogen cycles of past environments. , Furthermore, recent studies have incorporated ecosystem models to quantitively interpret the isotopic data . The δ 13 C and δ 15 N uncertainties comprehensively evaluated for our analytical method will thus be the basis for future integration of compound-specific isotope analysis and model-based studies that would enable quantitative discussion on past biogeochemical cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The following parameters were determined: free and residual pyrolizable hydrocarbons (S 1 and S 2 , mg HC/g rock), oxygenated organic compounds content (S 3 , mg HC/g rock), hydrogen index (HI, 100*S 2 /TOC mg HC/g C org ), oxygen index (OI, 100*S 3 /TOC mg CO 2 /g C org ), T max (ºC), total organic carbon (TOC) content (wt%), hydrocarbon potential (SP, S 1 + S 2 , mg HC/g rock), and production index (PI, S 1 / S 1 + S 2 ) ( Table 1). The minimum TOC value for a sample to be characterized at least as an immature source rock is 0.5 wt% (Hunt 1979;Tissot and Welte 1984). Bitumen extraction was achieved using a Soxhlet apparatus, with a chloroform methanol mixture (90:10 v/v).…”
Section: Organic Geochemistrymentioning
confidence: 99%
“…Comparing the C 25 with the neighboring n-C 20 alkane it may be observed that the upper Kalamaki succession (evaporitic and Lago Mare) contains much more abundant middle-chain n-alkanes than the lower pre-evaporitic part of the section. This observation could indicate that the organic matter originates from grasses growing in marine and brackish coastal waters (Hunt 1996). This would imply that the upper Kalamaki section had an additional contribution of eukaryotes (mainly zooplankton, algae) and/or prokaryotes (bacteria) beyond the higher plants as organic matter input.…”
Section: Quality Type and Source Of Organic Mattermentioning
confidence: 99%